Evidence- and risk-based planning for food security under climate change - Lamanna, Christine; Ramírez Villegas, Julián Armando; Wijk, Mark T. van; Corner-Dolloff, Caitlin; Girvetz, Evan Hartunian; Rosenstock, Todd S. (2015)
Planning robust climate-smart development programs can be done today with existing information. We propose a risk-household-option modeling approach to address household food security under climate change in Africa. Through a case study in Niger, we demonstrate that prioritizing CSA is possible by taking into account livelihood status, risks, and potential effects of CSA practices.